2022
DOI: 10.1038/s41392-022-01058-z
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell homing and trafficking in tissues and tumors: from biology to application

Abstract: Natural killer (NK) cells, a subgroup of innate lymphoid cells, act as the first line of defense against cancer. Although some evidence shows that NK cells can develop in secondary lymphoid tissues, NK cells develop mainly in the bone marrow (BM) and egress into the blood circulation when they mature. They then migrate to and settle down in peripheral tissues, though some special subsets home back into the BM or secondary lymphoid organs. Owing to its success in allogeneic adoptive transfer for cancer treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 310 publications
(429 reference statements)
0
56
0
1
Order By: Relevance
“…Here, our study revealed that breast cancer patients in the high-risk group generally showed higher immune infiltration and greater enrichment of immune-related pathways than their counterparts in the low-risk group, indicating that the CRGs risk score model can distinguish the degree of immune infiltration in patients, and cancer-associated inflammation may play important roles in patient prognoses [ 44 ]. Of note, our data also suggested that NK cell activation may help to stratify subpopulation of patients, which makes it a promising new target for tumor immunotherapy [ 45 ]. Additionally, the comparison regarding immune escape between the high- and low-risk subgroups revealed that the high-risk group was associated with a higher potential for immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…Here, our study revealed that breast cancer patients in the high-risk group generally showed higher immune infiltration and greater enrichment of immune-related pathways than their counterparts in the low-risk group, indicating that the CRGs risk score model can distinguish the degree of immune infiltration in patients, and cancer-associated inflammation may play important roles in patient prognoses [ 44 ]. Of note, our data also suggested that NK cell activation may help to stratify subpopulation of patients, which makes it a promising new target for tumor immunotherapy [ 45 ]. Additionally, the comparison regarding immune escape between the high- and low-risk subgroups revealed that the high-risk group was associated with a higher potential for immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…dNK cells comprise about 70% of all feto-maternal interface lymphocytes during first-trimester pregnancy in humans, and they support trophoblast invasion and angiogenesis [82][83][84][85]. dNK cells in the uterus highly express CXCR3, with relatively low expression of CXCR4 [32]. Very low CXCR1, CXCR2, CX3CR1, or CCR1, 2, 3 expression has also been observed in dNK cells.…”
Section: Human Uterine Nk (Unk) Cellsmentioning
confidence: 99%
“…NK cells are characterized as CD3 − CD56 + large granular lymphocytes consisting of two broad subtypes: the naïve CD56 bright CD16 dim subsets and the more common and mature CD56 dim CD16 + subsets [8]. These cells are broadly distributed across the peripheral blood as well as the bone marrow, lymph nodes, spleen, and liver [9,10]. They partake in several critical roles in the human innate immune system, including surveillance and cytotoxic functions against tumor cells [1].…”
Section: Nk Cell Biologymentioning
confidence: 99%